The efficacy of trastuzumab deruxtecan in Chinese breast cancer patients: a real-world multicenter study - He, Miao; Liu, Xiaohui; Zhang, Yan; Shao, Zhenyu; Sun, Tiantian; Hu, Yu (Frontiers in Oncology, 2025)
IntroductionIn mainland China, trastuzumab deruxtecan was first authorized in February 2023 as a monotherapy for the treatment of patients with HER-2-positive adult breast cancer who were either unresectable or had metastasized after receiving one or more anti-HER-2 treatments. In July 2023, trastuzumab deruxtecan was approved for the treatment of patients with metastatic disease who had undergone at least one previous systemic therapy, as well as those with unresectable or metastatic adult breast cancer who had low expression of HER-2 and who had experienced a relapse within six months of finishing adjuvant chemotherapy.MethodsThe study included seven participants with HER-2 low expression breast cancer and eighteen participants with HER-2-positive advanced breast cancer from six study centers in Shandong Province, China. Efficacy and safety data on trastuzumab deruxtecan were also gathered. The study involved intravenous injection of trastuzumab deruxtecan at a dosage of 5.4 mg/kg every three weeks until the disease progressed or the drug's toxicity became unmanageable, whichever came first.Results and DiscussionDuring a 8-month follow-up period, the disease control rate for patients with HER-positive breast cancer was 88.89% (16/18). The disease control rate for patients with HER-2 low-expressing breast cancer was 85.71% (6/7). The most common adverse reactions were gastrointestinal reactions, such as nausea, which occurred in 64.00% (16/25), and interstitial lung disease, which had a probability of occurring in 4.00% (1/25). In this real-world study, trastuzumab deruxtecan showed favorable efficacy and safety in both HER-2-positive breast cancer and HER-2 low-expressing breast cancer.